Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

So I have this series:

$$\displaystyle\sum_{n=1}^{\infty}\frac{3n^2+15n+9}{n^4+6n^3+9n^2}$$

I noticed:

$$\displaystyle\sum_{n=1}^{\infty}\frac{1}{n^2}(\frac{3n^2+15n+9}{n^2+6n+9})$$

So can I say that it's convergent already or should I use a critera on the second fraction in the sum?

Also for sum I could use partial fractions or am I mistaken?

Any help would be appreciated.

share|cite|improve this question
    
Note that $n^2+6n+9=(n+3)^2$. Also, Wolfram Mathematica gives $\frac{115}{36}$ for the limit of your sum. – vrugtehagel Feb 15 at 14:03
    
also i can take 3 out of the numerator – MathIsTheWayOfLife Feb 15 at 14:05
    
Unless you are looking to find the exact sum, you should be able to do a direct comparison test to something like $\sum\frac{1}{n^2}$. If finding how to correctly use the inequalities in this case is difficult, then a ratio test might be easier. – JMoravitz Feb 15 at 14:08
    
thank you , i appreciate it – MathIsTheWayOfLife Feb 15 at 14:11
    
And... $$\sum_{n=1}^{\infty}\frac{1}{n^2}\cdot\frac{3n^2+15n+9}{n^2+6n+9} = \sum_{n=1}^{\infty}\frac{3}{n^2}\cdot\frac{n^2+5n+3}{n^2+6n+9} = 3\sum_{n=1}^{\infty}\frac{1}{n^2}\left(1 - \frac{n+6}{n^2+6n+9}\right)$$ ...which may help you, or may be not. – CiaPan Feb 15 at 14:59
up vote 10 down vote accepted

You can conclude that the series converges by the comparison test. We can also calculate the sum. Note that $$\frac{3n^{2}+15n+9}{n^{4}+6n^{3}+9n^{2}}=\frac{1}{n^{2}}+\frac{1}{n}-\frac{1}{n+3}-\frac{1}{\left(n+3\right)^{2}} $$ hence $$\sum_{n\geq1}\frac{3n^{2}+15n+9}{n^{4}+6n^{3}+9n^{2}}=\sum_{n\geq1}\left(\frac{1}{n^{2}}+\frac{1}{n}-\frac{1}{n+3}-\frac{1}{\left(n+3\right)^{2}}\right)$$ $$=2+\frac{1}{2}+\frac{1}{4}+\frac{1}{3}+\frac{1}{9} =\frac{115}{36} $$ because the series telescopes.

share|cite|improve this answer

Consider

\begin{align} a_n=\frac{3n^2+15n+9}{n^4+6n^3+9n^2} &\le \frac{3n^2+15n^2+9n^2}{n^2(n+3)^2} \\ &= \frac{27}{(n+3)^2}\\ &\le \frac{27}{n^2} = b_n \end{align}

It is well know that

$$\sum_{n=1}^\infty \frac{1}{n^2}$$

converges. Since $0\le a_n\le b_n$ and $\sum b_n$ converges, we may conclude that $\sum a_n$ converges.

share|cite|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.